Study of genetic variation and its association with tensile strength among bamboo species through whole genome resequencing - Del Giudice, Lorenzo; Bazakos, Christos; Vassiliou, Michalis F. (Frontiers in Plant Science, 2022)
Moso bamboo (Phyllostachys edulis) is a versatile plant species that is widely used as a construction material by many low-income countries due to the lack of major construction materials such as steel and reinforced concrete. It is also widely used in China. Bamboo is an economical sustainable materi-al that behaves exceptionally in natural disasters like earthquakes and it can offer viable solutions for the contemporary engineering challenges. Despite bamboo’s potential in the engineering sector, bio-logical features such as, its long generation time, its large genome size and its polyploidy are con-straining factors for genetic and genomic studies that potentially can assist the breeding efforts. This study re-sequenced 8 Phyllostachys species and 18 natural accessions of Ph. edulis, generating a large set of functionally annotated molecular markers (SNPs and InDels) providing a key genomic resource information. Moreover, all this genomic information was used to carry out a preliminary genome wide association analysis and several candidate genes were identified to be correlated with a mechanical property that is of high interest to structural engineers: its tensile strength normal to its fibers (i.e. splitting).